SIMULATION OF THE OPERATION OF PRODUCTION OF PISCO IN A BATCH DISTILLATION COLUMN PACKED STAINLESS STEEL - Otiniano C., M. (2013)
It presents a model based on the Rayleigh equation to simulate the production of pisco using a batch distillation column packed stainless steel without reflux from grape quebranta of valley of Cañete. Model results are compared with experimental data. The results show that the proposed model can simulate the production of pisco.